Must improved labor standards hurt accumulation in the targeted sector? Stylized analysis of a developing economy - Arslan Razmi (University of Massachusetts, Department of Economics, 2009)
This paper analyzes a stylized small open economy. The analysis classifies the economy into two tradable output-producing sectors: a manufacturing sector and a (mainly tourism-related) services sector. Assuming sectoral differences based on stylized facts, we explore the impact of higher labor standards in the manufacturing sector on the long-term prospects of the economy using comparative dynamic exercises to analyze changes in output, foreign direct investment, relative prices, sectoral distribution, and accumulation. We find, in particular, that imposing higher standards across the manufacturing sector could, in the long run, shift the structure of the domestic economy in favor of that sector.
Keywords: 330